(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Chronic Kidney Disease (CKD) includes many pathophysiological processes related to impaired renal function and decreased reformist Glomerular Filtration Rate (GFR). The rapid economic development and globalization have promoted the progress of epidemiology, which has led to rapid urbanization, major changes in lifestyle, and changes in eating habits. Regarding non-communicable or suspicious lifestyle diseases such as hypertension, diabetes, coronary artery disease, malignant tumor and Chronic Kidney Infection (CKD), here we describe in detail the CKD case of a 30-year-old patient. There is no direct description of infection in Ayurvedic science, so we can only compare the disease and Ayurvedic view points based on the comprehensible understanding of Ayurvedic cases. This is an agreement with a good cure effect. Guda-Ardrak (Electuarium Ginger-Jaggery) was used in Kalpa (a separate Ayurvedic therapy) with milk for 19 days. This seal exhibits reduced serum creatinine levels, increased appetite and increased alertness. This case study shows that Guda-Ardrak Kalpa is an effective CKD treatment option.